Potency of Concrete by Utilizing Coconut Fiber to Improve Strength of Concrete (International Journal of Innovative Research in Engineering & Management, 2023)
The recurring and abrupt collapse of  concrete structures as well as apparent cracks in buildings  underscores the importance of this study. The research  investigated the potential utilization of coconut fiber as a  strengthening material to augment the load-bearing  capacity of concrete. To achieve this, concrete beams  measuring 600mm x 150mm x 150mm were produced,  and coconut fiber was added in varying proportions of  1%, 2%, 3%, and 4% by weight as a partial substitute for  cement. Load testing was carried out on the samples  produced on days 7 and 28. The study revealed that  concrete M40 containing coconut fibers tends to exhibit  greater load resistance and is less prone to disintegration  after failure compared to conventional concrete.  Incorporating coconut fiber into concrete has the capability to transform the outlook of concrete by  increasing its load-bearing capacity and offering an  escape route in case of collapse, potentially  revolutionizing the future of concrete. The superior  properties of coconut fiber concrete compared to  traditional concrete suggest that it can be utilized in  structures designed to withstand seismic activity by  introducing a 2% replacement of cement with coconut  fiber to achieve greater strength.
Keywords: Concrete; Concrete Potency; Utilizing Coconut Fiber; Strength of Concrete; Coarse Sand